Effectiveness and safety of echinocandins combination therapy with the standard of care compared to the standard of care monotherapy for the treatment of invasive aspergillosis infection: a meta-analysis - Alsowaida, Yazed Saleh; Alshoumr, Bader; Alowais, Shuroug A.; Bin Saleh, Khalid; Alshammari, Alia; Alshurtan, Kareemah; Wali, Haytham A. (Frontiers in Pharmacology, 2024)
BackgroundThis meta-analysis aims to evaluate the effectiveness and safety of combining echinocandins with standard of care (SOC) antifungal drugs for treating invasive aspergillosis infection (IAI).MethodWe searched PubMed, Embase, and Cochrane Library from their inception to 25 July 2024. Our outcomes included clinical cure, mortality, and adverse drug reactions (ADRs). We compared echinocandins in combination with SOC antifungal agents against SOC monotherapy therapy. We used the random-effects model for the meta-analysis, and our estimated effects were reported as odds ratios (ORs) with 95% confidence intervals (CI).ResultsTen studies were included in our meta-analysis comprising 1100 patients: 415 were in the echinocandin combination groups, and 685 were in the SOC groups. The clinical cure rate (OR 1.35, 95% CI: 0.75–2.42, p = 0.27), mortality (OR 0.90, 95% CI: 0.50–1.63, p = 0.73), and ADRs rate (OR 0.95, 95% CI: 0.49–1.82, p = 0.87) were not statistically different in echinocandins combination with SOC compared to SOC monotherapy. Notably, there is a signal for a better clinical cure rate in echinocandins in combination with SOC.ConclusionOur meta-analysis found no differences in clinical cure and mortality rate when using combination therapy of echinocandin antifungal agents with the SOC compared to SOC monotherapy. However, there is a signal for better outcomes with the echinocandins combination group. The ADRs in the echinocandins combination group were not worse than SOC monotherapy.